Error analysis and language comparison as teaching strategies for German as a foreign language in a South African context - Anne Baker (Problemy Wczesnej Edukacji)
Since 2015 there has been increased protest action by students at South African universities. One of the issues is decolonizing the curriculum. Academics have been re-thinking the curricula of various academic offerings. Recognizing the African heritage of students studying German could be in the form of comparing the first language (L1) of black African learners with German in order to facilitate learning the target language (TL). Specific examples of similarities and differences between German and Zulu are addressed in this article.